Relationship between physical frailty, nutritional risk factors and protein intake in community-dwelling older adults. (June 2022) - Buhl, Sussi Friis; Beck, Anne Marie; Olsen, Pia Øllgaard; Kock, Gry; Christensen, Britt; Wegner, Manfred; Vaarst, Jonathan; Caserotti, Paolo
Summary: Background & aims: Physical frailty may compromise physical function and reduce self-reliance in community-dwelling older adults. We investigated if nutritional risk factors and protein intake were associated with physical frailty in community-dwelling adults. Methods: This cross-sectional study combined data from two studies in community-dwelling adults ≥65 years. Variables included physical frailty (SHARE-FI75+), nutritional risk factors (dysphagia, poor dental status, illness, unintentional weight loss, low and high BMI), chronic diseases, physical function, and protein intake (4-day food records). Logistic regression analyses were performed to investigate the association between physical frailty, number of nutritional risk factors and specific nutritional risk factors, and between physical frailty and protein intake. Results: A total of 1430 participants were included in the study of these n = 860 were ≥80 years. Having one, two or more nutritional risk factors increased odds of physical pre-frail/frail condition (adjusted OR 1.39 95% CI 1.07–1.80; OR 2.67 1.76–4.04, respectively). Unintentional weight loss, poor dental status, dysphagia, and high BMI independently increased odds of physical pre-frail/frail condition. In participants ≥80 years two or more nutritional risk factors were associated with physical pre-frail/frail condition (adjusted OR 2.56 95%CI 1.45–4.52) and high BMI increased odds of physical pre-frail/frail condition independently. Higher intakes of protein did not significantly reduce odds of physical pre-frail/frail condition (adjusted OR 0.23 95% CI 0.05–1.09) in this sample of community-dwelling adults ≥80 years. Conclusion: Nutritional risk factors were independently associated with physical pre-frail/frail condition in community-dwelling older adults. Tackling nutritional risk factors offers an opportunity in primary prevention of malnutrition and physical frailty.